Social Jealousy and Stigma: Negative Externalities of Social Assistance Payments in Germany - Sonja C. Kassenböhmer; John P. Haisken-DeNew (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the role of social assistance payments (SAP or Sozialhilfe) in determining levels of life satisfaction in Germany using the SOEP 1995-2004. We find strong evidence that individuals in Germany are negatively influenced by increased SAP payments controlling for income, whether or not they actually receive such payments (stigma and social jealousy). While there are obvious benefits to making SAP to those needy, there are substantial negative externalities experienced by those who neither receive SAP nor qualify (counterfactual SAP). Furthermore, these negative effects are even stronger for those who do receive benefits (stigma) suggesting that social jealousy and stigma are a force to be reckoned with when evaluating social policy. We show that the added benefits of increasing SAP are reduced by 50 to 100% because of social jealousy and stigma costs, whereas child benefits (Kindergeld) are seen to enhance life satisfaction over and above a simple income effect. Further, own-earned income, over and above the SAP subsistence level is valued much higher than transfer payments at the SAP subsistence level, suggesting a policy focus on increasing employment integration efforts for SAP recipients as opposed merely to providing SAP transfers.
Keywords: I31; I38; J64; 330; Well Being; Life Satisfaction; Social Assistance; Stigma; Social Jealousy; Sozialhilfe; Soziale Ungleichheit; Sozialhilfeempfänger; Neid; Lebenszufriedenheit; Externer Effekt; Deutschland